The Community's Dynamics Towards Clean Water Adequacy and Membrane Technology in Bojonegoro, Indonesia - Setiyo Yuli Handono; Yusuf Wibisono; Wahyunanto Agung Nugroho; Chusnul Arif (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2023)
Fresh and clean water is an essential source of life. It can be supplied from the oceans, rivers, lakes, streams, and marshes. Nowadays, clean water availability has become a problem in several areas. Several problems usually occur, including the local ecosystem and air conditions, so they cannot be used properly. It is one area vulnerable to clean water availability. Meanwhile, UNESCO declares the community's right to clean water is 60 liters per person daily. This situation is the basis of research problems with the aim of (1) analyzing the problems and obstacles of the Nganti community towards water needs, (2) community responses to these problems and technology, and (3) the Nganti community strategies for now and future. The method used in this research was qualitative and descriptive. The key informants are the head of village, the head of the Clean Water Association, the head of Ngraho sub-district, the leader of community, and a survey of 40 Nganti-Ngraho residents. The data analysis used statistics descriptive and qualitative by using SMART method. The results show that the currently developed strategy was membrane technology, but the ultra-filtrated water was still turbid, requiring a more sophisticated membrane technology. The expected strategy is that local government institutions need to be directly involved to improve water quality.